Transceiver optimization for multi-user systems : rate improvement and degrees of freedom characterization - Zeng, Yong (2014)
This thesis is devoted to optimizing the transceiver strategies in multi-user wireless systems for maximizing the users' achievable rates and the degrees of freedom (DoF).